Model Penjadwalan Batch Multi Item dengan Dependent Processing Time - Sukoyo Sukoyo; TMA Ari Samadhi; Bermawi P. Iskandar; Abdul Hakim Halim (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2010)
This paper investigates a development of single machine batch scheduling for multi items with dependent processing time. The batch scheduling problem is to determine simultaneously number of batch (N), which item and its size allocated for each batch, and processing sequences of resulting batches. We use total actual flow time as the objective of schedule performance. The multi item batch scheduling problem could be formulated into a biner-integer nonlinear programming model because the number of batch should be in integer value, the allocation of items to resulting batch need binary values, and also there are some non-linearity on objective function and constraint due to the dependent processing time. By applying relaxation on the decision variable of number of batch (N) as parameter, a heuristic procedure could be applied to find solution of the single machine batch scheduling problem for multi items.